2020
DOI: 10.3389/fbioe.2020.00879
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Bioavailability and Stability of Curcumin Using Solid Lipid Nanoparticles (CLEN): A Covenant for Its Effectiveness

Abstract: Curcumin, very rightly referred to as "a wonder drug" is proven to be efficacious in a variety of inflammatory disorders including cancers. Antiaging, anti-inflammatory, antioxidant, antitumor, chemosensitizing, P-gp efflux inhibiting, and antiproliferative activity are some of the striking features of curcumin, highlighting its importance in chemotherapy. Curcumin inhibits Bcl-2, Bcl-XL, VEGF, c-Myc, ICAM-1, EGFR, STAT3 phosphorylation, and cyclin D1 genes involved in the various stages of breast, prostate, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…Despite trying to overcome that by additives and pharmacological combinations, investigations of these new formulas versus standard CUR are still not well researched (Lopresti, 2018). However, new nanoparticles showed positive results (Gupta et al, 2020). CUR has an antihyperlipidemic effect through its antioxidant effect and regulation of lipid metabolic genes (Zingg, Hasan, & Meydani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite trying to overcome that by additives and pharmacological combinations, investigations of these new formulas versus standard CUR are still not well researched (Lopresti, 2018). However, new nanoparticles showed positive results (Gupta et al, 2020). CUR has an antihyperlipidemic effect through its antioxidant effect and regulation of lipid metabolic genes (Zingg, Hasan, & Meydani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported 69.78 folds and 9 folds higher oral bioavailability as compared to free Curcumin and marketed formulation (CurcuWIN ® ). The results ensure the efficacy of Curcumin solid lipid nanoparticles in treating cancer and other inflammatory diseases [77] The nanometric size and complexity of colloidal populations are one of the reasons why polymorphic transitions have not been deciphered precisely. However advanced biophysical techniques such as cryo-and freeze-fracture transmission electron microscopy, SAXS, and SANS are being applied to study SLN structures.…”
Section: Solid Lipid Nanoparticles (Slns)mentioning
confidence: 92%
“…Several studies have shown that some antioxidants, such as lycopene [215], quercetin [216], curcumin [217], and astaxanthin [218] can be successfully loaded onto NLCs. Other studies revealed the successful encapsulation of resveratrol [219], idebenone [220], ferulic acid [221], and curcumin [222] on SLNs. Some of the most common techniques applied for the synthesis of SLNs and NLCs are presented in Figure 9 [209].…”
Section: Solid-lipid-based Nps and Nanostructured Lipid Carriersmentioning
confidence: 99%